Shock wave structure of multi-temperature Grad 10-moment equations for a binary gas mixture. (6th April 2021) - Bisi, M.; Groppi, M.; Macaluso, A.; Martalò, G.
Abstract: A multi-temperature formal hydrodynamic limit of kinetic equations, based on Grad-type approximation of the distribution functions, is employed for the analysis of the steady shock problem in a binary mixture. The presence of a singular barrier and its effects on the occurrence of either smooth profiles or of weak solutions with a discontinuity is investigated for varying Mach number. Some numerical simulations of mixtures of two noble gases are presented and commented on, with reference also to analogous phenomena in different model descriptions.